Family businesses and students of engineering: A low-achieving binomial - Quintana, M (Nexo Revista Científica, 2010)
Between August and September 2009 a statistical study was carried out in order to assess the connection between different types of family businesses and technology students at the National University of Engineering. The study researched the technological tools used by such businesses in relation to their economic activities. With this objective, a questionnaire was created and applied to students studying computer studies, electronic and electrical engineering who also had connections to family businesses (voluntary sample). Of the results obtained, it was found that within a total of 26 businesses (these being representative of the different economic sectors of the Country) the majority (96%) used technological tools either infrequently or not at all in both the production and administrative processes. This result reflects a lack of utilization of the capabilities and abilities available in the sector of society qualified in higher technological education by the small family business sector. This is shown by their infrequent utilization of technology as a support in production or commercial activities. The recommendations proposed in relation to these results have lead to the creation of a business plan directed towards the offer of the above mentioned technological services oriented towards support in the business sector in order to increase competitiveness. Keywords: familiar business; university; technology; small business. DOI: 10.5377/nexo.v22i2.44 Nexo Revista Científica Vol. 22, No. 02, pp.61-65/Diciembre 2009